Supply Chain Process of Environmental Information System: Exploratory Factor Analysis - Habidin, Nurul Fadly; Janudin, Sharul Effendy; Hudin, Norlaile Salleh; Md Zabit, Mohd Nazir; Mohd Fuzi, Nursyazwani; Ong, Sharon Yong Yee (International Journal of Supply Chain Management, 2019)
The purpose of this study is to identify the supply chain process of environmental information system (EIS) using the exploratory factor analysis (EFA). In this study, EFA was conducted on supply chain process of EIS constructs (technology and processes). 350 valid responses were used for final analysis, representing a response rate of 13.46%. These findings are expected to supports Malaysian manufacturing industry to implement key strategies with supply chain process of EIS. Hence, the supply chain process of EIS implementation may assist Malaysian manufacturing industry to increase the supply chain and information system in the organization.